2018
DOI: 10.1111/apa.14426
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products and their receptors did not show any association with body mass parameters in metabolically healthy adolescents

Abstract: HOMA-IR and the TG/HDL-C index were associated with BMI and inflammation markers. CML and sRAGE were not associated with obesity or inflammation. These parameters were higher in unhealthy obese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
7
1
1
Order By: Relevance
“…These results agree with another study that demonstrates that obese AGEs are significantly higher than non-obese (Antoniotti, et al [39] ). While disagreeing with other studies that stated that There was no correlation between obesity and circulating AGEs (Garay-Sevilla, et al [40] ). The effect of AGEs is classified as receptor-dependent via binding to the AGE receptor (RAGE) or receptorindependent (such as cross-links with extracellular matrix) (Haddad, et al [41] ).…”
Section: Discussioncontrasting
confidence: 60%
“…These results agree with another study that demonstrates that obese AGEs are significantly higher than non-obese (Antoniotti, et al [39] ). While disagreeing with other studies that stated that There was no correlation between obesity and circulating AGEs (Garay-Sevilla, et al [40] ). The effect of AGEs is classified as receptor-dependent via binding to the AGE receptor (RAGE) or receptorindependent (such as cross-links with extracellular matrix) (Haddad, et al [41] ).…”
Section: Discussioncontrasting
confidence: 60%
“…Other studies confirmed that obesity is associated with lower levels of sRAGE in pre-pubertal cohorts of children (23, 24) and reported that sRAGE was independently associated with liver steatosis (23) and carotid intima-media thickness (24). However, recently, other authors did not find any significant association between markers of obesity and AGEs or sRAGE (25).…”
Section: Discussionmentioning
confidence: 95%
“…Serum AGEs and sRAGE levels were not related to vascular complications in patients with prediabetes nor impaired glucose metabolism in patients with type 2 diabetes [78,79]. Although in higher levels, CML and sRAGE were also not associated with obesity or inflammation in unhealthy obese adolescents [80]. It is likely that total AGEs levels are not directly associated with insulin resistance or vascular complications, but modification of specific proteins or accumulation in tissue may by better markers of such complications.…”
Section: Evidence In Human Studiesmentioning
confidence: 91%